Comprehensive analysis on the influences of computer ethics on information security - Abdul Rahim, Fiza (2009)
Many ethical issues related to computer remains to be a concern regardless the mode of activity. Computer security, therefore, must also be concerned with the actions of trusted computer users. Since businesses have increased their usage of computers, an organization must play a major role in developing ethical awareness among employees so that they will make ethical choices regarding computer activities while in workplace. Therefore, the purposes of this project are to identify which component of computer ethics influence information security, to develop framework of computer ethics and information security and to determine the relationship between computer ethics and information security. Several statistical methods are used throughout the analysis. This project is expected provide an exposure on the importance of computer ethics and information security in an organization. Solutions need to be taken to deal with potential of unethical behavior associated with the use of information.